Filogenetik Ikan Kuro (Eleutheronema sp.) di Perairan Pesisir Merauke, Papua Selatan - Saleky, Dandi; Situmorang, Ferdinand C.; Welliken K., Marius A.; Pangaribuan, Rosa D. (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This research aims to identify kuro fish (Eleutheronema sp.) collected from the coastal waters of Merauke. Cytochrome Oxidase Subunit I (COI) Gene was amplified by the Polymerase Chain Reaction (PCR) method, using primers FISH F1 (5’-TCA ACC AAC CAC AAA GAC ATT GGC AC-3’) and FISH R1. (5’-TAG ACT TCT GGG TGG CCA AAG AAT CA -3’), while DNA data analysis uses Mega 11 software. Results research shows that DNA sequence obtained were 675 base pairs long with the identification result being Eleutheronema tetradactylum with a similarity level of 99.54 and 99.85% for each sample. Based on phylogenetic analysis and genetic distance, the two DNA sequences analyzed form the same clade with identification results with a genetic distance of 0.001. Analysis of genetic diversity found 2 haplotypes from the two samples. Both the Sample Have a small genetic distance because THEY are collected from the same waters DNA barcoding and phylogenetics can be used to identify species for management and conservation of species.